The Ominous Problem of the Two Nations: Two Solutions for the Regeneration of Society. Disraeli's Sybil and Carlyle's "Chartism" and Past and Present. - Chantal Cornut-Gentille D'Arcy (Miscelánea: A Journal of English and American Studies)
.